Comparative study of influence of two sperm preparation, swim up and density gradiant-swim up, on the outcomes of intrauterine insemination (IUI) in different types of semen samples infertile men referred to infertility research and treatment center, ACEC - lak, Elnaz; Lak, Elena; Hashemitabar, Mahmod; Afrogh, Mahsa; Nasirzadeh, Kamran; Shamolaghamsari, Fatemeh (Researcher Bulletin of Medical Sciences, 2020)
Infertility is one of the developing problems in most countries and it has a lot of problems, which can be emotional, social and political. Intrauterine insemination (IUI) is the first line Assisted Reproduction Treatment (ART) modality for infertile couples because this method is inexpensive and non-invasive, which is effective for the treatment of couples with unexplained infertility or patient with normal or mild male factor. Two methods, mainly considered as laboratory techniques for improving the quality of sperm, includes Swim-Up (SU) and Density Gradient Centrifugation (DGC). The SU is a common technique in IVF labs, and is mainly performed in a sample of semen having normal sperm concentration. In this technique, sperms are selected based on their motility and their capacity to leave the semen plasma. In the DGC method, sperms are selected based on the density, motile sperm are separated from dead sperms, leukocytes and other high-density semen plasmatic compounds. The aim of this method is thus to select sperms with high motility and morphology rates. Therefore, the aim of the present study is to compare the effect of these two methods on the outcome in intrauterine insemination in different groups, including normal samples (< 60 million (type1)) and 20-60 million/ml (type2), oligospermia (type3) and asthenospermia (type4), in patients referred to the Infertility Center. The present experimental study was performed on 545 couples who referred to the Infertility Research and Treatment Center, in 2016 for infertile reasons and were in a good status in terms of general health. Processing of sperm was done by two common methods, swim-up and Density Gradient Centrifugation according WHO. Our study showed the effectiveness of the Density gradient-Swim up technique compared to Swim-up as a sperm preparation method with a favourable IUI success.